Indocyanine green fluorescent lymphography during open inguinal hernia repair in a patient who developed postoperative ultrasonic hydrocele: A case report. (January 2022) - Nakaseko, Yuichi; Yoshida, Masashi; Kamada, Teppei; Nakashima, Keigo; Ohdaira, Hironori; Suzuki, Yutaka
Abstract: Background: To our knowledge, no reports of indocyanine green (ICG) fluorescent lymphography during inguinal hernia repair currently exist. We report the case of a patient who underwent ICG fluorescent lymphography during open inguinal hernia repair. Case presentation: A 63-year-old man was referred to our department for treatment of a right inguinal hernia, during which an ICG lymphography was performed. The patient had a history of robot-assisted radical prostatectomy for prostate cancer. Following induction of general anesthesia, 0.25 mg of ICG was injected into the right testicle and the scrotum was gently massaged, after which an open inguinal hernia repair was performed. During the operation, fluorescence from the ICG was observed in two lymphatic vessels in the spermatic cord. The ICG fluorescent vessels were resected due to the strong adhesion between the lymphatic vessels and the hernia sac. ICG leakage was observed in the resected vessels. An open tension-free technique was performed using an open mesh plug. The patient was discharged one day postoperatively. The histological diagnosis of the resected vessel was a lymphatic vessel. He had a slight postoperative hydrocele that was detected at the follow-up clinic 10 days postoperatively during ultrasonic examination (ultrasonic hydrocele). Conclusion: We report the use of ICG fluorescent lymphography during open inguinal hernia repair in a patient who developed postoperative ultrasonic hydrocele. This case may indicate a relationship between lymphatic vessel injury and hydrocele. Highlights: ICG fluorescent lymphography during open inguinal hernia repair is safe. It may be useful to prevent postoperative hydrocele. Lymphatic vessel injury and hydrocele may be related.